1999
DOI: 10.1161/01.atv.19.4.1066
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of Preβ 1 LpA1 and LpA4 Particles by Mast Cell Chymase Reduces Cholesterol Efflux From Macrophage Foam Cells Induced by Plasma

Abstract: Abstract-Exposure of the LpA1-containing particles present in HDL 3 and plasma to a minimal degree of proteolysis by the neutral protease chymase from exocytosed rat mast cell granules (granule remnants) leads to a reduction in the high-affinity component of cholesterol efflux from macrophage foam cells. In this study, we demonstrate for the first time, a role for mast cell chymase in the depletion of the lipid-poor minor components of HDL that are specifically involved in reverse cholesterol transport as init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
24
1
2

Year Published

2000
2000
2010
2010

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 64 publications
2
24
1
2
Order By: Relevance
“…Theoretically, these might include catabolism by cells, although tissue culture studies have indicated that this is unlikely to be quantitatively significant. 39 Because pre-␤ HDLs are more susceptible to proteolysis than are other HDLs, 40 they might be degraded by enzymes released into tissue fluid, 41,42 although no apoA-I fragments were detected in our HP-SEC fractions of lymph. A third possibility is that some small pre-␤ HDLs are converted in tissue fluid into larger discoidal species that are incompletely resolved by our laboratory procedures, as a consequence of uptake of cell-derived PL and UC.…”
Section: Nanjee Et Almentioning
confidence: 92%
“…Theoretically, these might include catabolism by cells, although tissue culture studies have indicated that this is unlikely to be quantitatively significant. 39 Because pre-␤ HDLs are more susceptible to proteolysis than are other HDLs, 40 they might be degraded by enzymes released into tissue fluid, 41,42 although no apoA-I fragments were detected in our HP-SEC fractions of lymph. A third possibility is that some small pre-␤ HDLs are converted in tissue fluid into larger discoidal species that are incompletely resolved by our laboratory procedures, as a consequence of uptake of cell-derived PL and UC.…”
Section: Nanjee Et Almentioning
confidence: 92%
“…Furthermore, studies in vitro have demonstrated that chymase specifically depletes preb-HDL particles (26), thus blocking cholesterol efflux mediated by the ABCA1 pathway (27). In contrast, limited proteolysis of HDL 3 particles by chymase does not impair their ability to activate LCAT (28) or to act as phospholipid acceptors in PLTP-mediated phospholipid transfer reactions (29).…”
mentioning
confidence: 99%
“…Efflux of UC from cells to pre-␤ 0 -HDLs in tissue fluids exceeds its esterification, leading to accumulation of UC-rich discoidal HDLs in lymph (16,17 ). For this pathway of RCT, which presumably applies to arterial smooth muscle and macrophages, ABCA1 transporter function (4,18,19 ) and pre-␤-HDL concentration (20,21 ) appear to play critical roles in regulating UC efflux.…”
mentioning
confidence: 99%